A structural equation modeling analysis of relational governance and economic performance in agri-food supply chains: Evidence from the dairy sheep industry in Sardinia (Italy) - Luca Camanzi; Elisabetta Arba; Cosimo Rota; Cesare Zanasi; Giulio Malorgio (Agricultural and Food Economics, 2018)
This study investigates the factors affecting the inter-organizational relationships and governance of firms in agri-food supply chains and assesses the influence that the current conditions of vertical coordination have on the economic performance of these firms. Research hypotheses describing the causal effects between the environment, product characteristics, inter-organizational relationships, relational governance, and firm economic performance are formulated and tested using a structural equation modeling approach. Data were gathered from a questionnaire administered via a direct survey to both farmers and processors in a traditional high-quality dairy sheep supply chain in the Italian region of Sardinia: the Pecorino Romano Protected Designation of Origin. Results point out the role of informal contractual arrangements in this local production system characterized by social cohesion, entailing higher product quality and better economic performance. Further, the study highlights the role of trust as a key variable for attaining collaborative paths along the agri-food supply chain, particularly between farmers and processors.
Keywords: 330; Relational governance; Economic performance; Agri-food supply chain; Vertical coordination; Structural equation model; Direct survey; Pecorino Romano; Protected designation of origin (PDO); Marketing